EFFECT OF NITROGEN AND SULPHUR LEVELS ON GROWTH AND YIELD OF PEARLMILLET (Pennisetum glaucum L.) - POLUMURI RINI CAROLINE; SHIKHA SINGH (The Bioscan, 2021)
The field experiment was conducted during Zaid 2019 at Central Crop Research Farm, Department of Agronomy, SHUATS, Prayagraj (U.P.). The experiment was conducted to study the effect of nitrogen and sulphur levels on growth and yield of Pearl millet (Pennisetum glaucum L.) The experiment was laid out in Randomised block design comprising of 10 treatments and replicated thrice where, Nitrogen applied in three levels 40,60,80 kg/ha and Sulphur is also applied in three levels 15,20,25 kg/ha. The experimental results revealed that, maximum Plant height (166.33 cm), plant dry weight (59.54 g), ears/plant (4), grains /ear head (2172), grain yield (3.4 t/ha), stover yield (7.76 t/ha), and test weight (8.63 g) was obtained with the application of 80 Kg Nitrogen + 25 Kg Sulphur. The maximum harvest index (31.57 %), net return (¹ 111989.43) and B:C ratio (3.99) was obtained highest with application of 80 Kg N/ ha + 20 Kg S /ha. On the basis of one season experimentation, application of 80 Kg N/ ha along with 25 Kg S/ha is more productive whereas 80 Kg N/ha + 20 Kg S/ha was economically effective.